2011
DOI: 10.1007/s12687-011-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

A holistic approach to education programs in thalassemia for a multi-ethnic population: consideration of perspectives, attitudes, and perceived needs

Abstract: Hemoglobin disorders which include thalassemias are the most common heritable disorders. Effective treatment is available, and these disorders can be avoided as identification of carriers is achievable using simple hematological tests. An in-depth understanding of the awareness, attitudes, perceptions, and screening reservations towards thalassemia is necessary, as Malaysia has a multi-ethnic population with different religious beliefs. A total of 13 focus group discussions (70 participants) with members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 25 publications
(28 reference statements)
1
21
0
6
Order By: Relevance
“…It is also concerning that as a result of misunderstanding, many women from the current study believed they had been diagnosed with a medical condition, misattributed symptoms to this, and that some continued to worry about both their and their children's future health as a carrier. Similar misunderstanding was apparent amongst carriers detected in the antenatal screening program in England due to the terminology used (Locock and Kai 2008) and, in a study by Wong and colleagues, people in Malaysia described symptoms they associated with 'thalassaemia minor', such as pale skin and tiredness (Wong et al 2011). This suggests that the issue is not confined to the communication styles of Victorian healthcare practitioners, but reflects widespread practices in the education and care of those found to be carriers.…”
Section: Discussionmentioning
confidence: 88%
“…It is also concerning that as a result of misunderstanding, many women from the current study believed they had been diagnosed with a medical condition, misattributed symptoms to this, and that some continued to worry about both their and their children's future health as a carrier. Similar misunderstanding was apparent amongst carriers detected in the antenatal screening program in England due to the terminology used (Locock and Kai 2008) and, in a study by Wong and colleagues, people in Malaysia described symptoms they associated with 'thalassaemia minor', such as pale skin and tiredness (Wong et al 2011). This suggests that the issue is not confined to the communication styles of Victorian healthcare practitioners, but reflects widespread practices in the education and care of those found to be carriers.…”
Section: Discussionmentioning
confidence: 88%
“…The study by showed that audio-visual aids and personal experience sharing have been suggested as an effective means for communication and education among young adults. (18) Therefore, efforts to promote screening are of great interest to young adults. Thalassemia can be prevented by prenatal diagnosis, but selective abortion is not widely accepted by the public.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, preconceptional carrier screening is voluntary when it occurs in high schools and more often mandatory when applying for a marriage license (described as pre-marital screening) (Cousens et al 2010). These seem to be acceptable to the communities in which these approaches exist such as in Bahrain (Al Arrayed and Al Hajeri 2010) or in Malaysia where these might be implemented (Wong et al 2011a(Wong et al , 2011b. However, in the Netherlands where a screening program is not offered, there appeared to be a reluctance by GPs and midwives to facilitate the testing of at-risk ethnic groups, which could be a barrier to implementation (Weinreich et al 2009).…”
Section: Carrier Screening For Haemoglobinopathiesmentioning
confidence: 99%